Sistemas agroflorestais no assentamento Bela Vista (Iperó, SP): contribuições e limitações sob a ótica de famílias agricultoras - Abdalla, Tatiana Graeml (Universidade Federal de São Carlos, 2023)
Agroecology is a counter-hegemonic proposal to the agro-industrial production model, with peasant family farming playing a protagonist role in the pursuit of sustainable, healthy, and fair food production. Agroforestry Systems (AFS) are a set of management techniques that, when following agroecological principles, are capable of promoting various nature contributions to people (NCPs). However, the success of their objectives depends on factors such as the level of community participation, the design of these agroecosystems, and the available resources. The aim of this study was to examine the implementation of agroforestry systems on the plots of four settled families through government-funded projects, as well as to analyze the outcomes of these activities. An observant participation was carried out, in which participatory activities were conducted with each family. The gathered data went through a content analysis, complemented by a brief document analysis of each project's proposals. Family traditions of pesticide-free cultivation and partnerships' contribution seem to have been key elements for families' adherence to the projects, in addition to the resources offered by the latter. Families’ expectations over AFS were mainly food produce and income generation, which were only partially achieved. The satisfaction with the experience seems greater in cases where the practice was directed more towards self-consumption and less to commercialization. Other project limitations were the lack of continuity and technical assistance, the definition of a plot as a demonstration unit (unevenly distributing the collective workforce), and AFS designs with narrow interlines (hindering productivity and the use of machinery in the long run). Despite that, families reported contributions from the projects such as learning new agroecological techniques and strengthening the habit of planting trees. Regarding AFS management, scarcity of labor (affected by the health and demographic composition of families), insufficient collective workforce, anthropogenic fire, leaf-cutting ants, climate aspects, and pesticides application in neighboring properties were limiting factors. However, even if not always productive, AFS and trees play a relevant role in families' lives, and aspects such as aesthetic appreciation, affective memories, concerns for environmental issues, and the possibility of leaving wood for their children in the future contribute to their maintenance on the plots. Farmers deemed it crucial for upcoming initiatives to offer direct compensation for labor utilized in agroforestry systems, to promote equitable opportunities for all participants, and to establish long-term action plans Additionally, it is necessary for projects to conduct a more in-depth analysis of the individual and collective realities in which the beneficiary community is located, and for society to adopt policies that value the regulatory contributions of AFS to people and ensure their production flow in order to enable the continuation of their management by families.
Agroforestry systems in Bela Vista settlement (Iperó, SP): contributions and limitations from farming families' perspectives
Keywords: Agrofloresta; Assentamentos rurais; Pesquisa participativa; Manejo; Análise temática; Agroforestry; Rural settlement; Participatory research; Management; Thematic analysis; CIENCIAS AGRARIAS